Functional analysis of MSH2 unclassified variants found in suspected Lynch syndrome patients reveals pathogenicity due to attenuated mismatch repair. Issue 4 (5th February 2014) - Wielders, Eva AL; Hettinger, Jan; Dekker, Rob; Kets, C Marleen; Ligtenberg, Marjolijn J; Mensenkamp, Arjen R; van den Ouweland, Ans MW; Prins, Judith; Wagner, Anja; Dinjens, Winand NM; Dubbink, Hendrikus Jan; van Hest, Liselotte P; et al.
Abstract : Background: Lynch syndrome, an autosomal-dominant disorder characterised by high colorectal and endometrial cancer risks, is caused by inherited mutations in DNA mismatch repair (MMR) genes. Mutations fully abrogating gene function are unambiguously disease causing. However, missense mutations often have unknown functional implications, hampering genetic counselling. We have applied a novel approach to study three MSH2 unclassified variants (UVs) found in Dutch families with suspected Lynch syndrome. Methods: The three mutations were recreated in the endogenous Msh2 gene in mouse embryonic stem cells by oligonucleotide-directed gene modification. The effect of the UVs on MMR activity was then tested using a set of functional assays interrogating the main MMR functions. Results: We recreated and functionally tested three MSH2 UVs: MSH2-Y165D (c.493T>G), MSH2-Q690E (c.2068C>G) and MSH2-M813V (c.2437A>G). We observed reduced levels of MSH2-Y165D and MSH2-Q690E but not MSH2-M813V proteins. MSH2-M813V was able to support all MMR functions similar to wild-type MSH2, whereas MSH2-Y165D and MSH2-Q690E showed partial defects. Conclusions: Based on the results from our functional assays, we conclude that the MSH2-M813V variant is not disease causing. The MSH2-Y165D and MSH2-Q690E variants affect MMR function and are therefore likely the underlying cause of familial cancer predisposition. Since the MMR defect is partial, these variants may represent low penetrance alleles.